2017
DOI: 10.4103/2277-9175.190980
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Two Phenolic Compounds from a Moderately Cytotoxic Fraction of Cousinia verbascifolia Bunge

Abstract: Background:Little information is available about chemical components of the Cousinia genus. A primary cytotoxicity screening on Cousinia verbascifolia showed moderate cytotoxic activity against OVCAR-3 ovarian and HT-29 colon cancer cells. Therefore, the aim of this study is a phytochemical investigation to identify the compounds responsible for this bioactivity.Materials and Methods:Extraction was done through percolation and fractionations by reverse phase column chromatography and normal column chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The 1 H-NMR spectrum displayed two meta coupled doublets at δ H 6.26 (1H, d, J = 1.6 Hz) and 6.45 (1H, d, J = 1.6 Hz) attributed to H-6 and H-8, a singlet proton at δ H 6.51 (1H, s, H-3) two ortho coupled proton signals at δ H 6.97 (1H, d, J = 8. 4 Hz) and 7.33 (1H, dd, J = 8.4, 2.0 Hz), corresponding to H-5′ and H-6′ as well as δ 7.41 (1H, d, J = 2.0 Hz) corresponding to H-2′ proton, indicated that compound 1 is 3′,4′, 5 7 tetrahydroxy flavone known as luteolin in agreement with literature data and co-TLC with authenticated sample( 18 19 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The 1 H-NMR spectrum displayed two meta coupled doublets at δ H 6.26 (1H, d, J = 1.6 Hz) and 6.45 (1H, d, J = 1.6 Hz) attributed to H-6 and H-8, a singlet proton at δ H 6.51 (1H, s, H-3) two ortho coupled proton signals at δ H 6.97 (1H, d, J = 8. 4 Hz) and 7.33 (1H, dd, J = 8.4, 2.0 Hz), corresponding to H-5′ and H-6′ as well as δ 7.41 (1H, d, J = 2.0 Hz) corresponding to H-2′ proton, indicated that compound 1 is 3′,4′, 5 7 tetrahydroxy flavone known as luteolin in agreement with literature data and co-TLC with authenticated sample( 18 19 ).…”
Section: Discussionsupporting
confidence: 83%
“…The 1 H-NMR spectrum displayed two meta doublets at δ 6.10 (1H, d, J = 2.0 Hz), and 6.36 (1H, d, J = 2.0 Hz) coupled to each other similar to those of H-8 and H-6 in flavones in addition to a singlet proton at 6.49 (H-3), and two ortho -coupled signals at δ 6.83 (2H, d, J = 8. 8 Hz) and 7.75 (2H, d, J = 8.8 Hz), describing to H-6′,2′ and H-5′, 3′ related to AA′BB′ spin system indicated that compound 3 is 4′, 5 7-trihydroxyflavone or apigenin( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its UV spectrum showed two absorptions maxima at 340.7 and 265.5 nm which is characteristic for flavones. (13). Phytochemical analysis of other fractions (Fr1-Fr3, and Fr5) was also performed in another research work which its data were published elsewhere (14).…”
Section: Analysis Of Bioactive Fractionmentioning
confidence: 99%
“…Myricetin and quercetin inhibited mammalian TrxRs with IC 50 values of 0.62 and 0.97 Mmol/L, respectively [92]. Apigenin has been reported to arrest HT29 colon cancer [50]. Oncamex showed a strong anti-tumor effect against breast cancer while hesperetin was active against lung and carcinoma cancer cells [93].…”
Section: Monanthotaxis Littoralismentioning
confidence: 99%